2004
DOI: 10.1162/153535004773861723
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Respiratory-Gated Micro-CT Imaging in Small-Animal Oncology Models

Abstract: Micro-computed tomography(micro-CT) is becoming an accepted research tool for the noninvasive examination of laboratory animals such as mice and rats, but to date, in vivo scanning has largely been limited to the evaluation of skeletal tissues. We use a commercially available micro-CT device to perform respiratory gated in vivo acquisitions suitable for thoracic imaging. The instrument is described, along with the scan protocol and animal preparation techniques. Preliminary results confirm that lung tumors as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 21 publications
2
120
0
Order By: Relevance
“…A "mini" CT scanner that is scaled to a proportional voxel resolution in a mouse (with a 20 mm thoracic diameter) would involve voxels ‫ف‬ 75 m in diameter. The mouse's lungs have a combined volume of about 1.3 cm 3 ; therefore, in the mouse a 3D volume of at least 2 cm 3 must be imaged to capture the entire lung. How-ever, the mouse heart and respiratory rate are much higher than in humans, so cardio-respiratory dynamic processes are much more difficult to image in mice than in humans (3) because the micro-CT scan durations are generally limited by the rate of X-ray production.…”
mentioning
confidence: 99%
“…A "mini" CT scanner that is scaled to a proportional voxel resolution in a mouse (with a 20 mm thoracic diameter) would involve voxels ‫ف‬ 75 m in diameter. The mouse's lungs have a combined volume of about 1.3 cm 3 ; therefore, in the mouse a 3D volume of at least 2 cm 3 must be imaged to capture the entire lung. How-ever, the mouse heart and respiratory rate are much higher than in humans, so cardio-respiratory dynamic processes are much more difficult to image in mice than in humans (3) because the micro-CT scan durations are generally limited by the rate of X-ray production.…”
mentioning
confidence: 99%
“…Notwithstanding, the impact high dose CT has on longitudinal experimental results remains controversial. Studies often report opposing findings from no effects regarding dose delivered to tumors during longitudinal studies to results indicating high doses can induce tumor inhibition [19,20,[34][35][36]. Using a Mediso nanoPET/CT scanner, we found that for both the air/water and the TEM phantoms, decreasing CT dose resulted in visual image quality degradation and high noise, but had a relatively minimal impact on HU quantification, while adversely increasing small animal absorbed dose.…”
Section: Discussionmentioning
confidence: 74%
“…Micro-CT systems providing high-resolution images ($50 mm) and rapid data acquisition (typically 5-30 min) are emerging as a cost-effective means for detecting soft-tissue structures, skeletal abnormalities, and tumors in small animals (24,(45)(46)(47). The use of iodinated contrast agents enhances the weak endogenous contrast between different soft tissues.…”
Section: Micro-computed Tomography (Micro-ct)mentioning
confidence: 99%